Relationship between Knowledge about Fe Tablets and the Incidence of Anemia in Pregnant Women in the Third Trimester at the Bumi Aji Health Center, Central Lampung - Sari, Althof; Yulivantina, Eka Vicky; Hanifa, Fatya Nurul (Universitas Prima Indonesia, 2025)
Iron deficiency anemia in mothers can harm the fetus/baby's growth and development during and after pregnancy. To prevent this, every pregnant woman should take at least 90 blood supplement tablets (TTD). Iron tablets are crucial for fetal growth, as pregnancy increases the mother's blood volume, requiring more iron for nutrition and oxygen supply to the fetus. A quantitative cross-sectional design is used in this study, targeting all TM III pregnant women at the Bumi Aji Community Health Center in Central Lampung. A total of 46 individuals were selected through total sampling. Univariate analysis utilized a table of frequency distribution, and bivariate analysis was conducted using the Chi-Square test. The research results, categorized by inclusion and exclusion samples, highlighted the respondents' age and education level. A questionnaire was used to assess maternal knowledge regarding Fe tablets and their link to anemia. The study found a relationship between knowledge of Fe tablets and anemia among third trimester pregnant women at the Bumi Aji Community Health Center, Central Lampung, in 2024, using the ChiSquare method for calculations. There is a link between knowledge of Fe tablets and anemia in pregnant women in the third trimester at the Bumi Aji Health Center, Central Lampung in 2024, with an ap value of 0.008.